X-ray photoelectron spectroscopy : an introduction to principles and practices - Van der Heide, Paul, 1962- (Hoboken, N.J. : Wiley, 2012)
'This book introduces readers interested in the field of X-ray Photoelectron Spectroscopy (XPS) to the practical concepts in this field. The book first introduces the reader to the language and concepts used in this field and then demonstrates how these concepts are applied. Including how the spectra are produced, factors that can influence the spectra (all initial and final state effects are discussed), how to derive speciation, volume analysed and how one controls this (includes depth profiling), and quantification along with background substraction and curve fitting methodologies. This is presented in a concise yet comprehensive manner and each section is prepared such that they can be read independently of each other, and all equations are presented using the most commonly used units. Greater emphasis has been placed on spectral understanding/interpretation. For completeness sake, a description of commonly used instrumentation is also presented. Finally, some complementary surface analytical techniques and associated concepts are reviewed for comparative purposes in stand-alone appendix sections'--
'This book introduces readers interested in the field of X-ray Photoelectron Spectroscopy (XPS) to the practical concepts in this field. The book first introduces the reader to the language and concepts used in this field and then demonstrates how these concepts are applied'--
Machine generated contents note: ForewardPrefaceAcknowledgementsTable of ContentsList of Relevant ConstantsChapter 1. Introduction to XPS/ESCAChapter 2. Atoms, Ions and their Electronic StructureChapter 3. XPS InstrumentationChapter 4. Data Collection and QuantificationChapter 5. Spectral Interpretation for SpeciationChapter 6. Some Case StudiesAppendicesTechnique Acronym ListsXPS Instrumental Based AbbreviationsGlossary of TermsQuestions and AnswersList of XPS VendorsReferencesIndexNotes .
Includes bibliographical references and index.
Keywords: X-ray photoelectron spectroscopy